Quantitative assessment of iteratively denoised 3D SPACE with inner-volume excitation and simultaneous multi-slice BLADE for optimizing female pelvis magnetic resonance imaging at 1.5 T - Hausmann, Daniel; Pindur, Alexandra; Todorski, Inga; Weiland, Elisabeth; Kuehn, Bernd; Zhou, Kun; Bosshard, Lars; Prummer, Michael; Kubik-Huch, Rahel A. (Academic radiology, 2023)
Rationale and objectives - High-resolution T2-weighted magnetic resonance imaging (MRI) of the pelvis is the main technique used for diagnosing benign and malignant uterine diseases. However, the procedure may be time-consuming and requires training and experience. Therefore, this study was performed to compare the image quality of standard clinical BLADE (stBLADE) with a prototypical accelerated simultaneous multi-slice (SMS) BLADE procedure with either improved temporal resolution (tr) at the same slice thickness (SL) or improved spatial resolution (sr) with the same examination time and a prototypical isotropic 3D SPACE procedure with inner-volume excitation and iterative denoising. - Materials and methods - Patients who underwent clinically indicated MRI of the uterus were included in this prospective study and underwent stBLADE (acquisition time, 2 min 59 s; SL, 4 mm) and SMS BLADE (tr) with the same SL (4 mm) but reduced examination time (1 min 20 s) as well as SMS BLADE (sr) with thinner slices (3 mm) and comparable examination time (3 min 16 s). In addition, 3D SPACE was acquired in a sagittal orientation (5 min 36 s). The short axis of the cervix and the long axis of the corpus uteri were reconstructed in 1-mm and 3-mm SLs, retrospectively. Subjective overall image impression, delineation of anatomy/organs, lesion demarcation, and motion artifacts were assessed using a 5-point Likert scale and compared among the different techniques. The preferred sequence was then selected by three independent assessors. - Results - The analysis was based on 38 women (mean age, 44 ± 15 years). The overall image impression was similar for stBLADE, SMS BLADE (sr), and SMS BLADE (tr) but was significantly lower for 3D SPACE than stBLADE (p = 0.01). SMS BLADE (sr) was considered the preferred sequence because of slightly better performance in terms of overall image impression, organ delineation, and lesion demarcation, but without statistical significance. Both SMS BLADE (tr) and (sr) produced significantly fewer motion artifacts than stBLADE (p < 0.01 and p = 0.01), with no significant difference between SMS BLADE (tr) and (sr), while 3D SPACE had a significantly lower rating than stBLADE (p < 0.01). Image quality was rated as the least diagnostic criterion in all sequences and all cases. - Conclusion - SMS BLADE (sr) was the preferred sequence for MRI of the female pelvis, with higher sr than stBLADE. SMS BLADE (tr) may also be used to reduce the acquisition time without compromising image quality. Despite its lower image quality, 3D SPACE can also reduce the examination time and improve the workflow because of the possibility of retrospective multiplanar reconstructions.
Online verfügbar: 20. Juli 2022, Artikelversion: 15. Mai 2023
Gesehen am 19.08.2024